2018
DOI: 10.3390/ijms19102872
|View full text |Cite
|
Sign up to set email alerts
|

Hanks-Type Serine/Threonine Protein Kinases and Phosphatases in Bacteria: Roles in Signaling and Adaptation to Various Environments

Abstract: Reversible phosphorylation is a key mechanism that regulates many cellular processes in prokaryotes and eukaryotes. In prokaryotes, signal transduction includes two-component signaling systems, which involve a membrane sensor histidine kinase and a cognate DNA-binding response regulator. Several recent studies indicate that alternative regulatory pathways controlled by Hanks-type serine/threonine kinases (STKs) and serine/threonine phosphatases (STPs) also play an essential role in regulation of many different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 213 publications
(207 reference statements)
0
58
0
Order By: Relevance
“…An increasing number of important bacterial proteins have been shown to undergo post-translational modifications (PTMs), such as phosphorylation or acetylation [209][210][211]. M. tuberculosis ParB is phosphorylated by Serine/Threonine Protein Kinases (STPKs), including PknB, a key component of the signal transduction pathway that regulates, for example, cell division and the survival of the pathogen in the host [212,213].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…An increasing number of important bacterial proteins have been shown to undergo post-translational modifications (PTMs), such as phosphorylation or acetylation [209][210][211]. M. tuberculosis ParB is phosphorylated by Serine/Threonine Protein Kinases (STPKs), including PknB, a key component of the signal transduction pathway that regulates, for example, cell division and the survival of the pathogen in the host [212,213].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…These kinases often control the expression of certain genes [39]. However, Hanks-type STKs have been found in an array of prokaryotic organisms where their genomic abundance is often correlated with genome size, physiological and ecophysiological complexity, and ability to tolerate complex environments [14,38,40]. These STKs are implicated in the regulation of various aspects of bacterial physiology through post-translational modification of proteins, which may themselves be components of phosphorelay and transcriptional regulatory pathways [40][41][42][43].…”
Section: Function Of Multidomain Variable Proteinsmentioning
confidence: 99%
“…The most abundant signaling systems in bacteria including pneumococci are two-component regulatory systems consisting of a histidine kinase coupled to a cognate response regulator (Jung et al, 2012;Gómez-Mejia et al, 2017). However, previously published studies have demonstrated that eukaryotic-type Ser/Thr protein kinases (ESTKs) as well as Ser/Thr phosphatases (ESTPs) are present in a wide range of bacterial species and operate in parallel or overlapping signaling networks thereby constituting another important signaling mechanism for the regulation of different cellular functions (Shi et al, 2014;Wright and Ulijasz, 2014;Zhang et al, 2017;Janczarek et al, 2018). The pneumococcus presents only one gene encoding an ESTK, stkP, and its respective ESTP, phpP.…”
Section: Introductionmentioning
confidence: 99%